2019
DOI: 10.1093/carcin/bgz132
|View full text |Cite
|
Sign up to set email alerts
|

A trans-fatty acid-rich diet promotes liver tumorigenesis in HCV core gene transgenic mice

Abstract: Excess consumption of trans-fatty acid (TFA), an unsaturated fatty acid containing trans double bonds, is a major risk factor for cardiovascular disease and metabolic syndrome. However, little is known about the link between TFA and hepatocellular carcinoma (HCC) despite it being a frequent form of cancer in humans. In this study, the impact of excessive dietary TFA on hepatic tumorigenesis was assessed using hepatitis C virus (HCV) core gene transgenic mice that spontaneously developed HCC. Male transgenic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…The finding of palmitelaidic acid in our FFA signatures is also intriguing, since it is a trans fatty acid whose major dietary sources are hydrogenated vegetable oils and dairy fats. Trans fatty acid-rich diets have been shown to increase liver tumorigenesis in mouse models [36]. Recent studies have also suggested that lipid desaturation (i.e., formation of double bonds in the fatty acyl chains) also occurs more frequently in cancer cells, providing additional opportunities to interfere with cancer cell fatty acid metabolism by targeting the desaturase enzymes [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of palmitelaidic acid in our FFA signatures is also intriguing, since it is a trans fatty acid whose major dietary sources are hydrogenated vegetable oils and dairy fats. Trans fatty acid-rich diets have been shown to increase liver tumorigenesis in mouse models [36]. Recent studies have also suggested that lipid desaturation (i.e., formation of double bonds in the fatty acyl chains) also occurs more frequently in cancer cells, providing additional opportunities to interfere with cancer cell fatty acid metabolism by targeting the desaturase enzymes [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The diet was purchased from Research Diets Inc. (New Brunswick, NJ, USA). Mice in the former group were also used as the controls in the other studies [16,17]. A 30% decrease in food was selected as the DR intervention for the following two reasons: (1) a 30% food reduction protocol was reported to attenuate obesity and improve metabolic profiles without malnutrition in previous studies [10,11]; (2) this DR dose maintained the mouse body weight constant for the long term, preventing age-dependent body weight gain as determined by preliminary studies.…”
Section: Mice and Treatmentmentioning
confidence: 99%
“…Total liver lipids were extracted according to the hexane:isopropanol method [18] and measured using the identical kits (Wako Pure Chemical Industries Ltd). Hepatic hydroxyproline concentrations were measured using the QuickZyme Hydroxyproline Assay kit (QuickZyme BioSciences, Leiden, The Netherlands) as described elsewhere [16,17].…”
Section: Biochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations